2008
DOI: 10.1310/hct0906-407
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Subcutaneous Fat, Lipid Profile, and Parameters of Mitochondrial Toxicity in Patients with Peripheral Lipoatrophy When Stavudine is Switched to Tenofovir (LIPOTEST Study)

Abstract: In this study, switching from stavudine to tenofovir maintained durable virologic suppression when the HAART regimen included a protease inhibitor or a non-nucleoside reverse transcriptase inhibitor, led to a slow improvement of lipoatrophy, and improved the lipid profile and lactate levels with excellent tolerability. These results support the proactive change of stavudine to tenofovir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 35 publications
6
37
2
3
Order By: Relevance
“…[53][54][55][56] Other studies have reported a lowering of mitochondrial dysfunction when drug regimens were changed and NRTIs were replaced with tenofovir. [57][58][59] A recent study in rats found that very high doses (ie, 100 mg/kg/day) of tenofovir reduced mitochondrial DNA and gene expression in kidney cells. 60 The relevance of this observation given the very high dosing used is unclear.…”
Section: Mechanisms Of Tenofovir-associated Bone Lossmentioning
confidence: 99%
“…[53][54][55][56] Other studies have reported a lowering of mitochondrial dysfunction when drug regimens were changed and NRTIs were replaced with tenofovir. [57][58][59] A recent study in rats found that very high doses (ie, 100 mg/kg/day) of tenofovir reduced mitochondrial DNA and gene expression in kidney cells. 60 The relevance of this observation given the very high dosing used is unclear.…”
Section: Mechanisms Of Tenofovir-associated Bone Lossmentioning
confidence: 99%
“…Although few studies relating exclusively to facial lipoatrophy, a study conducted in Spain involving sixty-two patients with this type of Lipoatrophy, showed a similar distribution, with 71% of male patients [20].…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have associated the use of Stavudine to the occurrence of lipodystrophy and more specifically to Facial Lipoatrophy [10,20,31,32,33]. Recent studies have demonstrated that Efavirenz is also associated with the onset and progression of lipoatrophy [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have confirmed the metabolically beneficial effects of d4T switching [15][16][17]. Although most of these studies focussed on fat distribution and adipocyte function, it is reasonable to assume that mitochondrial liver function would also be improved by switching to a less toxic NRTI backbone.…”
Section: Discussionmentioning
confidence: 99%